1985
DOI: 10.1071/bi9850411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Factors on the Metabolism of Glucose by Preimplantation Mouse Embryos in vitro

Abstract: The metabolism of glucose by late pre implantation mouse embryos was studied in a variety of media whose composition had been changed to reflect the environmental conditions in the uterus more closely than do standard culture media. The effects of combinations of energy substrates, the presence or absence of amino acids and the level of potassium in the medium were investigated.The use of energy substrates for in vitro culture at levels present in the uterine environment resulted in rates of synthesis and degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…One important functional difference between them is that GLUT3 may transport glucose at a higher rate than GLUT1, 58,59 potentially seven times faster, and therefore may be better suited to transport maternal glucose into the preimplantation embryo that encounters a low-glucose (1 mmol/L) environment. 56,60 GLUT1 is then proposed to transport glucose into the embryonic cells for metabolism. 56 Our investigations of facilitative glucose transporters in ES cells found that both GLUT1 and GLUT3 were expressed, whereas GLUTs 2, 4, and 9 were not.…”
Section: Discussionmentioning
confidence: 99%
“…One important functional difference between them is that GLUT3 may transport glucose at a higher rate than GLUT1, 58,59 potentially seven times faster, and therefore may be better suited to transport maternal glucose into the preimplantation embryo that encounters a low-glucose (1 mmol/L) environment. 56,60 GLUT1 is then proposed to transport glucose into the embryonic cells for metabolism. 56 Our investigations of facilitative glucose transporters in ES cells found that both GLUT1 and GLUT3 were expressed, whereas GLUTs 2, 4, and 9 were not.…”
Section: Discussionmentioning
confidence: 99%
“…The GLUT most likely to be expressed in an apical location in TE and therefore responsible for the uptake of maternal glucose was GLUT3. Primarily found in neurons (13)(14)(15), this isoform has an apical distribution in other polarized epithelial cells (11,12) and its extremely low K m [10.6 Ϯ 1.3 mM for 3-OMG (10)], matching that of blastocysts would ensure efficient glucose uptake by the embryo at the low glucose levels prevailing in the uterus (16).…”
mentioning
confidence: 99%
“…Although the mouse blastocyst is capable of metabolizing exogenous steroid hormones (225), there is limited data on the direct action of hormones on the early embryo (226)(227)(228)(229). Certainly, estradiol appears to have a direct negative impact on mouse embryo development (230,231).…”
Section: Hormones and Growth Factorsmentioning
confidence: 99%